(untitled) (Revista Brasileira de Contabilidade e Gestão, 2013)
This paper presents a comparative study of two techniques for machine-learning concepts with artificial intelligence, using Neural Networks and Fuzzy controllers to classify data from patients undergoing surgery for removal of cancerous breast nodules. Process of data classification can be simple or complex depending on both the problem domain as well as the quality of available data. The accuracy of the results may also vary according to the problem domain, and some cases may permit a greater or lesser margin of error. The objective of this work is to demonstrate both the processes of data classification by a fuzzy approach and by using Neural networks, and also demonstrate how the techniques achieved the best results and with what settings.